COLLABORATIVE TEACHING CULTURES OF ENGLISH LECTURERS IN INDONESIAN POLYTECHNICS - Rosmaladewi, Rosmaladewi; Abduh, Amirullah (Universitas Negeri Makassar, 2017)
This paper aims to explore collaborative culture in three polytechnics in South Sulawesi. This study applied an interpretive qualitative case study of nine English lecturers using interviews, documents and observations. Drawing from Hargreaves and Fullanâ€™s (2012) collaborative cultural concept, this study finds that contrived collegiality is more dominance rather than genuine collaborative learning culture. This finding suggests that collaborative culture is structured formally and bureaucratically. This impact on the way lecturers perform their teaching, norms and their values.Â